Acceleration of MRI of the vocal tract provides additional insight into articulator modifications. Issue 4 (3rd February 2015) - Burdumy, Michael; Traser, Louisa; Richter, Bernhard; Echternach, Matthias; Korvink, Jan G.; Hennig, Jürgen; Zaitsev, Maxim
<x xml:space="preserve">Abstract</x> Purpose To accelerate dynamic imaging of the vocal tract during articulation. Materials and Methods Five subjects were imaged by magnetic resonance imaging (MRI) while repeating the word "Partikel" at 90 beats per minute, using both a radio‐frequency‐spoiled radial gradient echo sequence with golden angle projection rotation and a previously applied real‐time Cartesian sequence. The acquired data were reconstructed using a CG‐SENSE method and Cartesian reconstruction. The images from both methods were compared by measuring distances between anatomical landmarks that are important for resonance behavior of the vocal tract. Only commonly available hardware and software were used. Results With the presented radial method a spatial resolution of 1.8 mm at 25 frames per second could be achieved. Overall, the morphometric measurements of the vocal tract showed less deviation for the radial sequence both across repetitions and for all subjects. Fast modifications, such as complete lip closing, could be analyzed with greater fidelity using the high temporal resolution of the radial sequence. Conclusion The results indicate that higher temporal resolution is a necessity to catch fast morphometric changes in the vocal tract. J. Magn. Reson. Imaging 2015;42:925–935.